Aplicação da análise de sobrevivência na estimativa da vida útil de componentes construtivos - Maior, Célio Costa Souto (2009)
This Work was developed as an effort to utilize the techniques and concepts that are employed in Survival Analysis in medicine, in order to apply them in Civil Engineering in the construction area. These techniques is called Reliability, which allows estimating the life time of building components through probabilistic models commonly used in that area. These models were developed and applied to the collected data, with a reliability of 95%. This subject, in this area have been studied in the scientific community, but specifically in the construction area is poorly known and is still in its beginning and, deserves further study. Thus, our proposition was to take some benefit or some information that might help for future work from analysis of a sample to study. 60 samples were collected for study, and 10 of them were censored, so that the study ended with a predetermined number of samples. The results were obtained using the software R and compared the models Exponential, Weibull and Log-normal, with the Kaplan-Meier estimator showing both graphically and through tests, which model best fits the data collected. The model that best fitted was the lognormal